Transparency and Accountability of Islamic Pension Funds: A Systematic Review of the Literature - Fidya Puji Ramadhani; Taufiqur Rahman (Penerbit Hellow Pustaka, 2025)
This study aims to systematically analyze the literature related to the transparency and accountability of Islamic pension funds. Using a Systematic Literature Review (SLR) approach with the PRISMA protocol, this study identifies Islamic pension fund management practices, financial reporting mechanisms, the role of the Sharia Supervisory Board (SSB), technology implementation, and Sharia audit standards. A literature search was conducted in the Scopus, Web of Science, Emerald, EBSCO, and SINTA databases, covering the period 2013-2024, yielding 25 relevant articles for analysis after a screening process. The results indicate that the transparency of Islamic pension funds still faces challenges in terms of reporting standardization, investment information disclosure, and Sharia supervision. The integration of technologies such as blockchain and AI is beginning to be implemented to enhance transparency, although this is still limited to countries with advanced Islamic financial systems. This study contributes to the development of a comprehensive accountability framework for Islamic pension funds and identifies areas for future research in the context of the evolution of the global Islamic finance industry.